The Impact of Implementing Omnimbus Law On The Industrial Revolution 4.0 in Indonesia - Adelia Setya Ayu; Yudho Taruno Muryanto (The International Conference on Education, Social Sciences and Technology (ICESST), 2024)
In the era of industrial revolution 4.0, the whole world is experiencing very rapid development. This industrial revolution was the driving force for the creation of globalization which influenced many aspects of life. The era of information technology places human life in the midst of rapid technological developments. Technological advances have also brought changes to the legal system in Indonesia. The Indonesian legal system follows the civil law legal system and has undergone adjustments to apply the existing legal system in countries that adhere to the common law legal system. This is clearly seen with the Omnibus Law which aims to simplify regulations to make it easier for business entities to apply for permits to open their businesses in Indonesia and increase investment in the country. Technological changes in the industrial revolution era have brought changes to the Indonesian legal system with the implementation of different legal systems to answer the challenges of this industrial era.